Pengaruh Kegiatan Penambangan Timah terhadap Kualitas Air Laut di Wilayah Pesisir Kabupaten Bangka Provinsi Kepulauan Bangka Belitung - Kurniawan Kurniawan; Supriharyono Supriharyono; Dwi P. Sasongko (Department of Aquatic Resources Management, Faculty of Agriculture, Fisheries, and Biology, University of Bangka Belitung, 2014)
Tin mining activities in Bangka regency coastal areas are directly or indirectly give pressure significantly to the degradation of aquatic ecosystems including coral reef ecosystems that affect spawning, feeding, fishing ground of fish resources and other marine biota. The purpose of this study is to examine the content of heavy metals Pb, Cd, Cr in wastewater from tin mining activities in the coastal waters of Bangka Regency, to examine the content of heavy metals Pb, Cd, Cr of the sea waters which is tin mining activities occurred in the coastal area of Bangka Regency and to examine the content of heavy metals Pb, Cd, Cr in the sediments which is tin mining activities occurred in the coastal area of Bangka Regency. Methods of research conducted by direct observation in the field, data collection and laboratory testing. Data taken in the form of water quality parameters, residual waste leaching, sea water and sediment which caught in active tin mining areas. The content of heavy metals test results compared to heavy metal environmental quality standards for marine biota water based Kep 51/MENLH/2004 and the sediment by IADC / CEDA. The measurement results of water quality parameters are as follows: TSS value was on environmental quality standards (20 mg/l). There are 109 mg/l, 208 mg/l, 65 mg/l, 75 mg/l, 120 mg/l, 188 mg/l and 63 mg/l; Brightness was on environmental quality standards (SNI 05-2413-1991 less than 5 m) ranged from 0.05 to 0.08 m; Temperature 28-320C standard is still appropriate; salinity standards are ranging from 27 to 29 o/oo; Density Oxygen (DO) 7 to 9.8 ppm standard is 5 ppm (SNI 06-6989. 14-2004); The Degree of Acidity (pH) 6 to 7 pH is still qualify. The content of heavy metals (Pb, Cd, Cr) in wastewater from tin mining activities was on environmental quality standards that has become environmental pollutants. The content of heavy metals (Pb, Cd, Cr) in the seawater which is tin mining activities occurred in the coastal area of Bangka Regency have been on the environmental quality standards that has been categorized as polluted seawater. The content of heavy metals (Pb, Cd, Cr) in the sediment remained below the environmental quality standards of heavy metal content in the sediment